The Rose-Colored Glasses of Geriatric Fall Patients: Inconsistencies Between Knowledge of Risk Factors for and Actual Causes of Falls. (October 2020) - Collins, Courtney E.; Chandra, Arnav; Nguyen, Bryan; Schultz, Kurt; Mathew, Pawan; Chen, Tiffany; Renshaw, Savannah; Rose, Karen M.; Santry, Heena P.
Background: Falls are the leading cause of fatal injury, and most common cause of non-fatal trauma, among older adults. We sought to elicit older patient's perspectives on fall risks for the general population as well as contributions to any personal falls to identify opportunities to improve fall education. Methods: Ten patients with a history of falls from inpatient trauma and outpatient geriatric services were interviewed. Transcripts were analyzed independently by five individuals using triangulation and constant comparison (NVivo11, QSR International) to compare fall risks to fall causes. Results: All patients reported that either they (9/10 participants) or someone they knew (8/10) had fallen. Despite this, only two personally worried about falling. Patient perceptions of fall risks fell into seven major themes: physiologic decline (8/10); underestimating limitations (7/10); environmental hazards (7/10), lack of awareness/rushing (4/10), misuse/lack of walking aids (3/10); positional transitions (2/10), and improper footwear (1/10). In contrast, the most commonly reported causes of personal falls were lack of awareness/rushing (7/10), environmental hazards (3/10), misuse/lack of walking aids (2/10), improper footwear (2/10), physiologic decline (2/10), underestimating limitations (1/10) and positional transitions (1/10). In general tended to attribute their own falls to their surroundings and were less likely to attribute physical or psychological limitations. Conclusion: Despite participants identifying falls as a serious problem, they were unlikely to worry about falling themselves. Participants were able to identify common fall risks. However, when speaking about personal experience, they were more likely to blame environmental hazards or rushing, and minimized the role of physiologic decline and personal limitations.